A comparative study of [Ag11(iPrS)9(dppb)3]2+ and [Ag15S(sBuS)12(dppb)3]+: templating effect on structure and photoluminescence. Issue 30 (15th July 2021) - Shen, Yang-Lin; Zhao, Pei; Jin, Jun-Ling; Han, Jun; Liu, Chen; Liu, Zheng; Ehara, Masahiro; Xie, Yun-Peng; Lu, Xing
Abstract : A comparative study of [Ag11 ( i PrS)9 (dppb)3 ] 2+ and [Ag15 S( s BuS)12 (dppb)3 ] + was conducted to elucidate the templating effects of an S 2− anion on the geometrical structure and photoluminescence of silver(i ) thiolate clusters. Abstract : Atomically precise silver clusters with tunable photoluminescence (PL) properties have attracted extensive attention due to their great value for basic science and future applications. Here, we report that the addition of a sulfido template into a triangular thiolated silver cluster [Ag11 ( i PrS)9 (dppb)3 ]·2CF3 SO3 ·CH3 OH (Ag11, dppb = 1, 4-bis(diphenylphosphino)butane), which is emissive at 660 nm under ambient conditions, produced another silver cluster [S@Ag15 ( s BuS)12 (dppb)3 ]·CF3 SO3 ·H2 O (Ag15 ) that displays 716 nm emission with a 56 nm redshift aided by the ligand sec-butyl mercaptan. The sulfido template, which affects the geometrical and electronic structures, results in a redshift of Ag11 room-temperature PL as a result of opening up the template-to-metal charge transfer (TMCT) and disturbing the electronic transition between the metal core and ligands at the periphery.